Calidad del servicio y valor percibido por el cliente del área de operaciones del Banco de Crédito del Perú - Agencia Huamachuco, año 2016 - Melendez Peña, Francisco Moisés (2017)
This thesis was carried out at the Credit Bank of Peru (BCP), Huamachuco Agency, Sánchez Carrión Province, La Libertad Region, Peru; the general objective is to determine the relationship between the quality of the service and the value perceived by the client of the area of operations of said bank. The research problem stated: What is the relationship between the quality of the service and the value perceived by the client of the Bank’s area of operations of Peru’s credit – Huamachuco Agency, year 2016? In the collection of data have taken into account the populations: 07 workers and 1100 clients of the area of operations; Samble one is composed of workers 07, and sample of 88 clients; having applied the respective surveys. According to the results obtained, using the Pearson Correlation Coefficient technique, the corresponding analysis and discussion have been carried out, thus demonstrating the validity of the hypothesis that: “The Quality of Service has a positive and significant relationship With the Customer Perceived Value of the Operations Area of the Bank of Credit of Peru – Huamachuco Agency, year 2016”. As the main conclusion is that the variables Quality of Service and Value Perceived by the Customer are related positively and significantly, that is to say as long as the bank provides a better Quality of Service through reliability, security, responsiveness, empathy and tangibility; this will generate that the Perceived Value by the Customer is also better both in the benefits and in the costs that the client assumes.